Rural structure change and rural energy efficiency - Li Jianhua; Jing Yongping (2011 International Conference on Business Management and Electronic Information, 2011)
Since 1978, the Chinese rural area has experienced deep structure changes: the ratio of commercial crops to grain crops, the ratio of the added value of forestry, animal husbandry, side-line production and fishery to the added value of farming, the ratio of non-agriculture investment to agriculture investment in rural area. Using the data from 1978 to 2007, effects of these structure changes upon the efficiency of energy consumption in Chinese rural area was assessed. The empirical result showed some evidence. Some policy suggestion based on analysis was advised.